Electrical Ground Impedance Measurements in Alaskan Permafrost Regions. - Hoekstra,Pieter (1975)
The objective of the work described in the report is to establish the techniques leading to construction of an electrical conductivity map of Alaska in the V/L/MF frequency band for use in planning of navigational aids. Several difficulties were encountered in using ground conductivity data of high quality to construct a conductivity map of Alaska. They are: (a) The results showed that the ground conductivity in permafrost areas of North America is very heterogeneous, so that it is not directly apparent how to assign an effective conductivity value to a path of practical length (about 100 km); and, (b) The geological and permafrost conditions very much in Alaska, so that measurements at a location are representative of a small area only, leaving large areas of Alaska open to question. Theoretical evaluations of the seasonal changes in ground conductivity and their effect on radiowave propagation and electrical grounding are also discussed.